A Temperature Plasmonic Sensor Based on a Side Opening Hollow Fiber Filled with High Refractive Index Sensing Medium - Lei Zhao (Sensors, 2019)
A surface plasmon resonance temperature sensor based on a side opening hollow-core microstructured optical fiber is proposed in this paper. This design employs a gold nanowire to excite the plasmon mode, and can be easily filled with the sensing medium through the side opening of the fiber, which not only simplifies the fabrication of the sensor but can also use the high refractive index sensing medium. The coupling characteristics, sensing performance and fabrication tolerance of the sensor are analyzed by using the finite element method. The simulation results indicate that the maximum sensitivity is 3.21 nm/°C for the x-polarized core mode in the temperature range of 13.27−50.99 °C, and 4.98 nm/°C for the y-polarized core mode in the temperature range of 14.55−51.19 °C, when benzene is used as the sensing medium. The sensor also shows a good stability in the range of ±10% fabrication tolerance.